Fracture life & culture in the West, 1918-1938 - Blom, Philipp 1970- (Atlantic Books, 2015)
The award-winning author of The Vertigo Years argues that in the aftermath of World War I, Western culture redirected energies into hedonistic, aesthetic and intellectual adventures of self-discovery in ways that triggered world-changing innovations
Includes bibliographical references (pages 415-442) and index
Keywords: 1900 - 1999; Geschichte 1900-2000; Geschichte 1918-1938; History; Civilization; Geschichte; Kultur; Europe; Europa; USA; Europe -- History -- 1918-1945; Europe -- Civilization -- 20th century; United States -- History -- 1919-1933; United States -- History -- 1933-1945; Westliche Welt; 1900 - 1999 -- fast